«Puliamo San Siro»: lottare contro lo stigma territoriale in un quartiere di edilizia popolare di Milano - Paolo Grassi (Archivio Antropologico Mediterraneo)
Marginal neighbourhoods are often more exposed to environmental problems than the areas where urban elites live. A neighbourhood of social housing of Milan called San Siro – where I am carrying out an ethnographic research since January 2017 – seems to confirm this statement. In fact, in the last few years the public space of San Siro is getting more and more polluted. Trash is abandoned in several corners, streets are dirty and unclean. This paper will describe how two local committees tried to face this issue through distinct strategies. The first one (Comitato di Quartiere – Committee of the Neighbourhood) is formed by a group of elderly Italian residents; the second one (Comitato Abitanti – Committee of the Residents) is connected to the Milanese social movements that fight for housing rights. Despite their different visions, the two committees pursue a very similar objective when they implement actions aimed to set up a “clean” and “nice” public space: deconstructing the territorial stigma, i.e. demanding a spatial justice against their marginalization.